Teaching Arabic through the perspective of Maqasid Syariah / Abd Rahman Jamaan - Jamaan, Abd Rahman (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Arabic expresses both aspects of the Holy Qur'an and Sunnah; they are the main medium through which Islam is understood. Thus, Arabic plays a major role in interpreting the Qur'an and Sunnah because the language allows Muslims to interact directly with the sacred text of Islam without depending entirely on translations, which can, at times, be misleading (Al-Attas, 1980). Hence, the knowledge of the Arabic language empowers Muslims to appreciate the intended meaning, sense, and context for legal issues in the Qur'an and hadith. The Arabic tongue has maintained a significant position in the Islamic scientific tradition too. This language is indeed the main medium for the dissemination and elucidation of knowledge in interpretation, jurisprudence, philosophy, and Islamic science. For example, the works and treatises by scholars such as al-Ghazali and Ibn Sina were originally written in.